Synergistic effects of Mediterranean diet combined with phytosterol-based supplements and omega-3 fatty acids on lipid profiles: a pilot study in menopausal women - Cannella, Fabiana; Algaria, Elisa Assunta; Brunetti, Kashi; Del Quondam, Simona; Bottan, Diego; Cervia, Davide; Catalani, Elisabetta (Frontiers in Nutrition, 2025)
ObjectivesMenopause marks the cessation of ovarian function, preceded by perimenopause, a transitional phase characterized by hormonal fluctuations and metabolic changes, including dyslipidemia. Therefore, a targeted nutritional approach is essential. In this retrospective, observational, pilot study, we evaluated the impact of a Mediterranean-based dietary regimen supplemented with specific natural compounds on lipid profiles and body composition in perimenopausal and menopausal women with hypercholesterolemia.MethodsAn individual dietary plan based on the Mediterranean diet, supplemented with a phytosterol-based formula containing bergamot, prickly pear extract, and vitamin B1, was recommended for each study participant. Additionally, omega-3 fatty acid supplementation was recommended due to its well-documented benefits in reducing cardiovascular disease risk factors, including elevated lipid levels. Lipid profile, body composition, and anthropometric values were recorded and carefully analyzed.ResultsOur findings indicated that this combined dietary approach significantly improved lipid profiles, as evidenced by reductions in total cholesterol, low-density lipoprotein cholesterol, and triglycerides and by an increment in high-density lipoprotein cholesterol values. Furthermore, the dietary plan positively impacted overall body composition and morphometric parameters.ConclusionThese preliminary findings suggest that a personalized, nutritionally targeted approach may be an effective non-pharmacological strategy for managing cardiovascular and metabolic risk factors during the menopausal transition and postmenopausal period. Further large-scale, controlled studies are warranted to confirm these results and explore long-term outcomes.